The Effectiveness of Differentiated E-LKPD Using Liveworksheets on Junior High School Students’ Statistical Literacy in Data Presentation - Sari Muliawanti; Endang Wahyuningrum; Sudirman Sudirman (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Indonesian students’ low statistical literacy, as revealed by PISA 2022 with only 18% achieving Mathematics competency at level 2, presents an urgent educational challenge. The dominant use of printed teaching materials limits students’ digital learning experiences with varying levels of initial understanding. This study developed differentiated E-LKPD (Electronic Student Worksheets) using Liveworksheets on Data Presentation topics through Research and Development with ADDIE model. Participants were 7th grade students of SMP Gunungjati 1 Purwokerto in the 2024/2025 academic year. Data collection instruments included interview instruments, needs analysis questionnaires, validation questionnaires, student response questionnaires, and statistical literacy tests. The product achieved very high validity based on Aiken’s index for content (0.91), media (0.94), and language (0.90). Practicality received 86% with very practical criteria. The product’s effectiveness showed statistical literacy improvement with N-Gain of 0.60 (moderate). The differentiated E-LKPD using Liveworksheets proved valid, practical, and effective in enhancing statistical literacy skills of junior high school students. This digital, interactive approach successfully accommodates diverse student readiness levels, providing an innovative solution for personalized mathematics learning that bridges the gap between traditional instruction and students’ digital learning needs.